1969
DOI: 10.1177/107769906904600206
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences and Inoculation against Persuasion

Abstract: Source vs. message orientation produced no differences under either source- or message-immunization conditions, nor did sex. But self-esteem did interact with immunization strategies as predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…These findings offer further support for the robustness of inoculation, irrespective of message approach (Pfau, 1997). Extant research indicates that inoculation confers resistance to persuasion, whether treatments are constructed as same or different (McGuire, 1961(McGuire, , 1962(McGuire, , 1966Pfau, 1992;Pfau & Burgoon, 1988;Pfau et al, 1990;Pfau et al, 1997a), central or peripheral (Pfau et al, 1997a), content or source oriented (Freedman & Sears, 1965;Stone, 1969), or affective-positive or negative (Lee & Pfau, 1998), and now, as cognitive, affective-anger, or affective-happiness. Practitioners should find the robust- NOTE: Threat, anger, and attitude toward persuasive attacks were measured using 7-point scales (threat and attitude toward persuasive attack scales ranged from 1 to 7; anger scales from 0 to 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings offer further support for the robustness of inoculation, irrespective of message approach (Pfau, 1997). Extant research indicates that inoculation confers resistance to persuasion, whether treatments are constructed as same or different (McGuire, 1961(McGuire, , 1962(McGuire, , 1966Pfau, 1992;Pfau & Burgoon, 1988;Pfau et al, 1990;Pfau et al, 1997a), central or peripheral (Pfau et al, 1997a), content or source oriented (Freedman & Sears, 1965;Stone, 1969), or affective-positive or negative (Lee & Pfau, 1998), and now, as cognitive, affective-anger, or affective-happiness. Practitioners should find the robust- NOTE: Threat, anger, and attitude toward persuasive attacks were measured using 7-point scales (threat and attitude toward persuasive attack scales ranged from 1 to 7; anger scales from 0 to 6).…”
Section: Discussionmentioning
confidence: 99%
“…Whether researchers devise inoculation treatments that are cognitive or emotional, treatment messages feature similar threat components and should be capable of promoting resistance regardless of the message approach employed in the refutational preemption component of the messages. Indeed, research reveals that inoculation confers resistance to influence whether inoculation treatments are: same or different (see above), central or peripheral (Pfau et al, 1997b), content or source oriented (Freedman & Sears, 1965;Stone, 1969), or affective positive or affective negative (Lee & Pfau, 1998). Thus, this study predicts:…”
Section: Effectiveness Of Cognitive and Affective Inoculation Treatmentsmentioning
confidence: 99%
“…For example, one source of an attack message was described as ''incompetently staffed, riddled with political appointees, and generally not serving the public interest'' (Tannenbaum, Macaulay, & Norris, 1966, p. 234), while in another case the source was accused of ''unethical and unprofessional behavior'' (Tannenbaum & Norris, 1965, p. 150). Stone (1969) also tested the effectiveness of preemptive source derogation, comparing a source-derogation inoculation treatment condition with a messagederogation inoculation treatment. He posited that source-oriented individuals would be more influenced by source-derogation inoculation treatment messages and that message-oriented individuals would be more influenced by message-derogation inoculation treatment messages.…”
Section: Source Derogationmentioning
confidence: 99%
“…Alternatively, if communicators find themselves on the other side of an inoculation campaign—that is, as the source of attack messages—they may wish to consider low‐controlling, autonomy‐supportive language choices (Miller et al, 2007; Vansteenkiste, Lens, & Deci, 2006). Such messages might vary in language intensity depending on the passive versus active nature of inoculation pretreatments (Burgoon & Chase, 1973; Burgoon & King, 1974), or the source versus message focus of inoculations targeting high‐ versus low‐esteem receivers (Stone, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Stone (1969) called for inoculation research to focus more on attack message source derogation, Tannenbaum and colleagues compared the effectiveness of attack message source derogation and refutations independently and jointly (including two separate messages-one to generate source derogation followed by another to generate inoculation). They concluded that the greatest effects are experienced when the two are coupled and presented before the attack.…”
Section: Future Researchmentioning
confidence: 99%